PERBEDAAN KUNJUNGAN ANTENATAL CARE ANTARA IBU HAMIL PESERTA PROGAM KELUARGA HARAPAN (PKH) DAN BUKAN PESERTA PKH DI KECAMATAN KALISAT KABUPATEN JEMBER - Nika Nur Indah Sari; Andrei Ramani; Ni’mal Baroya (Fakultas Kesehatan Masyarakat, Universitas Jember, 2018)
Pregnant woman has a risk of mortality; therefore, it is necessary to prevent the maternal mortality by pregnancy test. PKH (Program Keluarga Harapan) is a program that supporta pregnancy test. This study aims to determine the different of antenatal care visits between pregnant women PKH participants and non PKH participants in Kalisat, Jember. This study was analytic with cross sectional approach. The data was analyzed by using chi-square test. The sample of this study were 36 pregnant women in each group randomized in 2016.The results showed that there was a significant difference between occupation status and accessibility to the antenatal care visit (completeness) between pregnant women PKH participants and non PKH participants where pregnant woman PKH participant who unemployed and have easy access are visit antenatal completely compared to pregnant woman non PKH participants. There is a difference between occupation status, husband support and accessibility to antenatal visit (accuracy) between pregnant women PKH participants and non PKH participants where pregnant woman PKH participants who unemployed have more visit antenatal care completely, and pregnant woman non-PKH participants with high husband support and easy accsess will be more appropriate visit compared with pregnant woman PKH participants. There were no differences in age, parity, education, family income, and medical history with antenatal care visit between pregnant women of PKH participants and non PKH participants.